Flavors of the sun : the Sahadi's guide to understanding, buying, and using Middle Eastern ingredients - Sahadi Whelan, Christine (Chronicle Books, 2021)
"Flavors of the Sun is both a deep dive into the diverse array of ingredients from the Middle East as well as the story of a beloved Brooklyn institution, Sahadi's. For the first time, the people behind Sahadi's are sharing their expert knowledge of these sought-after ingredients in the form of over 120 recipes, plus buying guides, and side bar "10 More Ways to Use..." sections"--